An opportunity cost approach to redundancy compensation: An application to Sri Lanka - Fiszbein, Ariel (Estudios de Economía, 2016)
The paper proposes the principles which should guide the design of a compensation package for redundant workers following a program of voluntary retrenchment. It is argued that the compensation should be equal to the opportunity cost of leaving the enterprise. Using a simple specification for the opportunity cost, a payment schedule is derived and simulated for the case of Sri Lanka.